In vivo toxicity of nitroaromatics: A comprehensive quantitative structure–activity relationship study. (21st March 2017) - Gooch, Aminah; Sizochenko, Natalia; Rasulev, Bakhtiyor; Gorb, Leonid; Leszczynski, Jerzy
Abstract: The toxicity data of 90 nitroaromatic compounds related to their 50% lethal dose concentration for rats (LD50) were analyzed to develop quantitative structure–activity relationship (QSAR) models. Quantum‐chemically calculated descriptors together with molecular descriptors generated by DRAGON, PaDEL, and HiT‐QSAR software were utilized to build QSAR models. Quality and validity of the models were determined by internal and external validation techniques. The results show that the toxicity of nitroaromatic compounds depends on various factors, such as the number of nitro‐groups, the topological state, and the presence of certain structural fragments. The developed models based on the largest (to date) dataset of nitroaromatics in vivo toxicity showed a good predictive ability. The results provide important input that could be applied in a preliminary assessment of nitroaromatic compounds' toxicity to mammals. Environ Toxicol Chem 2017;36:2227–2233. © 2017 SETAC